Unveiling the role of knowledge management effectiveness in university's performance through administrative departments’ innovation - Abu Elnasr E. Sobaih; Hassane Gharbi; Mohamed A. Ben Abdallah; Osama H. Mahmoud Hassan (Journal of Open Innovation: Technology, Market and Complexity)
In a highly competitive and challenging business environment, knowledge has been recognized as the lifeblood of any organization. It is crucial for organization’s survival in today’s competitive environment. Therefore, knowledge management is equally important as managing other resources and capabilities for gaining a competitive advantage. The issue of knowledge management has become a growing concern and hot topic for management research, especially in organisations like universities, where knowledge creation and management is essential. This paper investigates the link between knowledge management effectiveness, departments’ innovation, and performance of universities, through the case of King Faisal University (KFU). KFU was founded in 1975 by royal decree on the 6th of Jamada II, 1397 H, in Al-Hofuf, Al-Ahsa, Saudi Arabia and includes 16 colleges such as Business Administration, Art, Agriculture and Food Sciences, Veterinary, Clinical Pharmacy and Medicine. Based on an exploratory survey conducted among 115 participants from KFU, the results of structural model using SEM analysis reveal that knowledge management effectiveness significantly and positively influences departments’ innovation (β= 0.34, p < 0.001) and KFU performance (β= 0.572, p < 0.001). Additionally, departments’ innovation significantly and positively influences KFU performance (β= 0.37, p < 0.01). Furthermore, the results suggest that departments’ innovation acts as a mediator in the link between knowledge management effectiveness and performance of KFU (β= 0.129, with p = 0.021 <0.05). Various implications are then discussed for scholars and university administrators.